Omega-3 fatty acids. What consumers need to know - McManus, Alexandra; Merga, Margaret; Newton, Wendy (Elsevier, 2010)
The general public is increasingly aware of the health benefits associated with consumption of omega-3 fatty acids. While evidence of health benefits continues to mount, the underlying science is complex. Omega-3 fatty acids vary in their physiological efficacy. Consumers are typically unaware of differences in the efficacy of different omega-3 fatty acids and this lack of knowledge can result in consumers being misled within the marketplace. There is a need for consumers to be educated about the distinctions between omega-3 fatty acids. In the interim consumers remain at risk of purchasing premium fortified products and supplements that will not correspond to their desired health outcomes. This paper summarises the current understanding of fatty acid physiological metabolism and interaction for the purpose of highlighting this complex and multifaceted concern.